The Other Side of the “Istrian Exodus”: Immigration and Social Restoration in Slovenian Coastal Towns in the 1950s - Kalc, Aleksej (Two Homelands, 2019)
The article addresses the migration processes in the fifteen years after WWII in what is today’s Slovenian coastal region. The main emphasis is on the immigration following the annexation of this area to socialist Yugoslavia in 1954. The replacement of the population, the radical change of the ethnic structure and the geography of the immigration inflow are outlined. Some questions that affected the immigration and repopulation process are discussed and some possibilities for further research are presented, i.e. the policy and management of the migration processes, the inclusion patterns of the newcomers and the relationships among the indigenous and immigrant components.